2023
DOI: 10.3389/fmolb.2023.1051494
|View full text |Cite
|
Sign up to set email alerts
|

Conserved gene signatures shared among MAPT mutations reveal defects in calcium signaling

Abstract: Introduction: More than 50 mutations in the MAPT gene result in heterogeneous forms of frontotemporal lobar dementia with tau inclusions (FTLD-Tau). However, early pathogenic events that lead to disease and the degree to which they are common across MAPT mutations remain poorly understood. The goal of this study is to determine whether there is a common molecular signature of FTLD-Tau.Methods: We analyzed genes differentially expressed in induced pluripotent stem cell–derived neurons (iPSC-neurons) that repres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 144 publications
0
29
0
Order By: Relevance
“…LncRNAs can alter gene expression by cis or trans mechanisms. We found that the commonly differentially expressed lncRNAs were highly correlated with coding genes commonly differentially expressed in the presence of MAPT mutations (Minaya et al 2023). Gene enrichment analyses identified pathways related to Neurotrophin trk receptor signaling, Notch signaling, BDNF signaling, lipoprotein lipase activity, and axonal guidance.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…LncRNAs can alter gene expression by cis or trans mechanisms. We found that the commonly differentially expressed lncRNAs were highly correlated with coding genes commonly differentially expressed in the presence of MAPT mutations (Minaya et al 2023). Gene enrichment analyses identified pathways related to Neurotrophin trk receptor signaling, Notch signaling, BDNF signaling, lipoprotein lipase activity, and axonal guidance.…”
Section: Discussionmentioning
confidence: 96%
“…Differential gene expression analyses comparing controls with PSP and AD brains were performed using a “Simple Model” that employs multi-variable linear regression analyses using normalized gene expression measures and corrected by sex, age-at-death, RNA integrity number (RIN), brain tissue source, and flowcell as covariates (Allen et al 2016). Transcriptomic data from the middle temporal gyrus of FTLD-tau patients with MAPT IVS10+16 and p.P301L mutation ( MAPT IVS10+16 n=2 and MAPT p.P301L n=1) and neuropathology free controls (n=3) were also analyzed (Minaya et al 2023). Differential expression analyses comparing FTLD-tau mutation carrier brains with controls was performed using DESeq2 (v.1.22.2) R package (Love, Huber, and Anders 2014) as previously described (Minaya et al 2023).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations